2016
DOI: 10.1039/c5an02358k
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent nanoprobe for single bacterium tracking: functionalization of silver nanoparticles with tryptophan to probe the nanoparticle accumulation with single cell resolution

Abstract: The investigation of the interaction of silver nanoparticles and live bacteria cells is of particular importance for understanding and controlling their bactericidal properties. In this study, the process of internalization of silver nanoparticles in Escherichia coli cells was followed by means of synchrotron excitation deep ultraviolet (DUV) fluorescence imaging. Antimicrobial nanostructures that can absorb and emit light in the UV region were prepared by functionalization of silver nanoparticles with tryptop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Under these conditions, the photoluminescence of TiO 2 particles enables tracking their accumulation in bacteria with a higher spatial resolution compared to conventional optical methods ( Jamme et al, 2010 ). In previous works, this technique has been successfully employed to probe the distribution of antimicrobials in Enterobacter aerogenes ( Kašèáková et al, 2012 ) as well as the accumulation of tryptophan-functionalized gold and silver nanoparticles in E. coli ( Pajović et al, 2015 ; Dojčilović et al, 2016 ). Here, DUV fluorescence imaging with single-cell resolution revealed TiO 2 /cell co-localization by enabling to distinguish between the fluorescent signal pertaining to TiO 2 particles and the autofluorescence of treated E. coli or L. lactis bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the photoluminescence of TiO 2 particles enables tracking their accumulation in bacteria with a higher spatial resolution compared to conventional optical methods ( Jamme et al, 2010 ). In previous works, this technique has been successfully employed to probe the distribution of antimicrobials in Enterobacter aerogenes ( Kašèáková et al, 2012 ) as well as the accumulation of tryptophan-functionalized gold and silver nanoparticles in E. coli ( Pajović et al, 2015 ; Dojčilović et al, 2016 ). Here, DUV fluorescence imaging with single-cell resolution revealed TiO 2 /cell co-localization by enabling to distinguish between the fluorescent signal pertaining to TiO 2 particles and the autofluorescence of treated E. coli or L. lactis bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Deep ultraviolet fluorescence imaging of E. coli K12 MG1655 and L. lactis IBB477 cells after TiO 2 exposure was carried out on a Zeiss Axio Observer Z-1 microscope at the DISCO beamline ( Giuliani et al, 2009 ) of the SOLEIL synchrotron facility, as previously described for tryptophan-functionalized gold ( Pajović et al, 2015 ) and silver nanoparticles ( Dojčilović et al, 2016 ). Bacterial cells were cultured in appropriate medium containing TiO 2 at a concentration of 320 μg/mL (aggregated vs. dispersed forms, E171 vs. P25), collected at the stationary phase of growth and washed twice in phosphate buffered saline (5000 g, 5 min, room temperature).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of TrpAgNPs synthetized by a femtosecond laser system proved high bactericidal efficiency against E. coli . 24 Dojčilović et al 25 showed an increase in the intensity of fluorescence toward the interior of the cells, indicating that E. coli internalized the tryptophan functionalized nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…So far, structural techniques such as transmission electron microscopy [19], as well as noninvasive optical methods that include surface-enhanced Raman scattering, Rayleigh light scattering and confocal Raman microscopy [1], were used to investigate the nanoparticle-cell interactions and the migration of nanoparticles in cells. Our recent results demonstrated that synchrotron radiation deep-ultraviolet (DUV) fluorescence microscopy is a convenient method for determination of the accumulation of antibiotics [20,21,22,23,24], and nanoparticles [25,26,27,28,29] within an individual cell with a spatial resolution of ∼150 nm. For example, DUV fluorescent imaging studies of bacteria incubated with tryptophan functionalized silver [27] and gold [29] nanoparticles and showed that it was possible to distinguish the fluorescent signals of the nanostructures from the autofluorescence of the cells, due to a relatively simple morphology and small size (∼3 µm) of these prokaryotic cells.When it comes to more complex cells, such as human tissue cells, the signal differentiation is far from a trivial since the biomaterial is highly heterogeneous.…”
Section: Introductionmentioning
confidence: 99%